Empirical finance - Shigeyuki Hamori (MDPI, 2019)
There is no denying the role of empirical research in finance and the remarkable progress of empirical techniques in this research field. This Special Issue focuses on the broad topic of "Empirical Finance" and includes novel empirical research associated with financial data. One example includes the application of novel empirical techniques, such as machine learning, data mining, wavelet transform, copula analysis, and TV-VAR, to financial data. The Special Issue includes contributions on empirical finance, such as algorithmic trading, market efficiency, market microstructure, portfolio theory and asset allocation, asset pricing models, liquidity risk premium, currency crisis, return predictability, and volatility modeling.
Keywords: 650; Finanzmarkt; Wirtschaftsdaten; Data Mining; Multivariate Verteilung; Empirische Methode